Quality of soybeans stored in bag silo (Research, Society and Development, 2023)
The static storage capacity deficit has been one of the main bottlenecks in the grain production system in Brazil, and even more so in Mato Grosso, the main producing state. Thus, the search for storage alternatives becomes important, since investments in fixed infrastructure are high and take longer to materialize. The objective of this study was to evaluate the quality of soybeans stored in a silo bag for a period of 330 days. A bag silo with dimensions of 5 m in length and 1.5 m in height was used. The average initial water content of the grains was 10.5 %w.b. Samples were collected monthly and the physical, chemical and sanitary properties were evaluated, such as: moisture content, mass of 1,000 grains, bulk density, grain mass and volume, dry matter, ash and oil content, and incidence of associated fungi. There was no loss of physical quality of soybeans stored in silo bags. The dry matter content, oil and ash content did not show significant differences during storage. There was a trend towards a reduction in fungal incidence for most of the identified genera.